Transforming Trauma Resilience and Healing Through Our Connections With Animals - Tedeschi, Philip; Jenkins, Molly (Purdue University Press, 2019)
This book focuses on research developments, models, and practical applications of animal-assisted interventions for diverse populations who have experienced trauma. Physiological and psychological trauma is explored across three broad areas: 1) child maltreatment and family violence; 2) acute and post-traumatic stress, including that which is associated with military service, war, and developmental trauma; and 3) times of crisis, such as natural disasters and the ever-increasing risks associated with climate change, community violence, terrorism, and periods of personal loss and grief.Contributing authors, who include both national and international experts in the fields of human-animal connection and trauma, discuss how our relationships with animals can help build resiliency and foster healing to transform trauma and trauma response.